Peranan Guru Dalam Menerapkan Keterampilan Bertanya Di SD Negeri 56 Banda Aceh - Israwati, Israwati; Adnan, Adnan; Husin, M; Mustafa, Farha; Rahayu, Rahayu (Jurnal PGSD, 2020)
The role of teachers in applying questioning skills is carried out during learning The purpose of this study is to determine the role of teachers in applying questioning skills, obstacles and solutions in applying questioning skills in SD Negeri 56 Banda Aceh. Implementation, obstacles and solutions that are studied in this study are the roles that teachers do in applying questioning skills during learning. This research uses a qualitative research approach with descriptive research type. The subjects in this study were first grade to sixth grade teachers at SD Negeri 56 Banda Aceh. Data collection techniques are interviews, observation and documentation. Data analysis techniques used in this study were data analysis, data models (data display) and conclusion drawing / verification. The data validity technique used in this study is source triangulation. The observation of researchers at SD Negeri 56 Banda Aceh can be concluded that the teacher's questioning skills are the most frequent and most important activities carried out in the learning process. The ability to ask is the main ability that must be possessed by the teacher because asking is a tool for teaching. Because almost every stage of learning the teacher is required to ask questions, and the quality of the questions asked by the teacher will determine the quality of student answers. Giving questions will help students learn mentally and be more perfect in receiving information so students participate actively during the learning process